1976
DOI: 10.1002/j.1879-3479.1976.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bilateral Oophorectomy and Peroral Estradiol Valerate Therapy on Serum Lipids

Abstract: Punnonen, R., and Rauramo, L. (Dept. of Obstetrics and Gynaecology, University Hospital, Turku, Finland). Effect of bilateral oophorectomy and peroral estradiol valerate therapy on serum lipids. Int J Gynaecol Obstet 14:13-16, 1976.The effect of bilateral oophorectomy upon serum lipids was studied in 25 women, whose average age was 48 years. One month after castration the triglyceride level was significantly (p<0.01) higher than before the operation. Six months later the triglyceride level had fallen slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Ethinyl estrogens increase serum triglycerides (1,11,31) while non-alkylated estrogens in doses com monly used in replacement therapy post-menopausally do not. This has been dem onstrated both in women with natural menopause (19,(30)(31)(32) and after oophorec tomy (3, 25,29) in line with the present findings. From clinical experience it can be inferred that the given doses of EE and E2V are the lowest that, to a large extent, will extinguish or ameliorate estrogen-deficiency symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Ethinyl estrogens increase serum triglycerides (1,11,31) while non-alkylated estrogens in doses com monly used in replacement therapy post-menopausally do not. This has been dem onstrated both in women with natural menopause (19,(30)(31)(32) and after oophorec tomy (3, 25,29) in line with the present findings. From clinical experience it can be inferred that the given doses of EE and E2V are the lowest that, to a large extent, will extinguish or ameliorate estrogen-deficiency symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…This was achieved by enforcing a mythical concept that the early and late decelerations must be truly uniform (same in size and shape) [ 25 , 30 ] and gradual. Consequently, with near extinction of early and late decelerations, the midwives who are the front-line workers reported that CTG interpretation had become dysfunctional because of completely new-found difficulties in pattern recognition, thus affecting their performance and confidence [ 2 , 28 ]. On the other hand, many senior obstetricians have simply continued to interpret CTGs based on their past experience and conceptual understanding of the traditional British categorization of decelerations using the flexibility and discretion they can exercise [ 14-17 , 24 , 28 ].…”
Section: Misguided Discontinuation Of the Traditional British Categormentioning
confidence: 99%
“…Hence, decelerations which consistently occur during the contractions (most common) should not be called “variable”. But these get included anyway [ 2 , 13 ] because they are “rapid” and because all decelerations vary in depth and duration anyway! The reference given by FIGO (2015) [ 3 ] for this definition is the seminal paper of Ball and Parer [ 36 ].…”
Section: Critical Analysis Of Figo (2015) Definitions Of Decelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in triglycerides were not observed by all investigators, for others reported only an early increase in total cholesterol and LDL cholesterol [5]. However, major studies in ovariectomized women were realized at short term after castration, and it has been observed also that the lipid changes disappeared after a longer term [6]. Estrogens could act directly on the regulation of arterial cells, because 17/3-estradiol administered to ovariectomized monkeys inhibited coronary atherosclerosis independently of plasma lipid variations [7].…”
mentioning
confidence: 93%